The Settlements Pattern and Its Measurement Method - Agus Dwi Martono (Forum Geografi, 1996)
Settlement means a place (spatial) or an area where population conentrated on and live in together to make use of the environment to survive direct and develop their living. Pattern and distribution of the settlement constitute a closed connection. The settlement distribution deliberates the fact of where the settlement exists or is not obtainable in an area; while the settlement pattern constitutes a distribution characteristic which has much more connection with the effect of the economical historical and cultural factors. There are some measurement methods of the distribution pattern i.e with the neighborhood analysis formula (t) where if t = 0 it means the settlement pattern conentrates, t = 1 shows the random settlement pattern (uneven distribution), while if t = 2,15 shows the uniform (homogeneous) settelement pattern. The second method is the Demangoens Index (C) which only considers the total of the population, besides C score of the concentration, random, and uniform of the settlement pattern are not detected. Another measurement method is score per “grid square”. The method of R scale is also applicable in the measurement, in which R score is concerned with 0 – 2,1491; if score of R = 0,7 it shows that the settlement pattern would be in group; R = 0,7 – 1,4 means an uneven distribution and R = 1,4 – 2,1491 shows the evenly distribution of the settlement pattern.